2017
DOI: 10.1504/ijsom.2017.080676
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effect of supply chain role on the relationship between social capital and performance

Abstract: Abstract:The primary objective of this study is to examine the relationship between supply chain social capital and firm performance and whether the supply chain role of a firm (supplier, manufacturer, distributor, logistics provider) has a moderating effect on the positive relationship between the dimensions of social capital and the firm performance. The results show that three dimensions of social capital directly affect firm performance. Further, the supply chain role moderates the relationship between thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 27 publications
2
22
1
Order By: Relevance
“…For example, in servitized firms, social capital has been found to both directly, and indirectly through knowledge combination, enhance operational performance, however in traditional manufacturing firms it only improves operational performance indirectly through facilitating knowledge acquisition (Zhang et al, 2017). Leem and Rogers (2017) reported that for the supplier and distributor, only relational and cognitive capital positively influenced performance, whilst for the manufacturer and logistics, provider all the three dimensions of social capital improved performance.…”
Section: The Boundary Conditions Of Social Capital In Bsrsmentioning
confidence: 99%
“…For example, in servitized firms, social capital has been found to both directly, and indirectly through knowledge combination, enhance operational performance, however in traditional manufacturing firms it only improves operational performance indirectly through facilitating knowledge acquisition (Zhang et al, 2017). Leem and Rogers (2017) reported that for the supplier and distributor, only relational and cognitive capital positively influenced performance, whilst for the manufacturer and logistics, provider all the three dimensions of social capital improved performance.…”
Section: The Boundary Conditions Of Social Capital In Bsrsmentioning
confidence: 99%
“…While some research has shown that the pairing technique leads to the creativity and innovation of undergraduate students from a variety of majors and classes, including management and business (Nouri et al, 2013;Tadmor et al, 2012), there needs to be more research investigating how pairing contributes to the engagement of management and business students in deriving new ideas and solutions to problems in their field. Researchers have elucidated several issues and problems currently plaguing management in different industries, including education (Das and Mukherjee, 2017;Pors and Ratner, 2017), automobiles Gupta and Singh, 2017), agricultural engineering and natural resources (Najafabadi et al, 2017), the supply chain (Leem and Rogers, 2017), healthcare (Seppänen et al, 2017) and knowledge production (Ayuba and Haynes, 2017). Assigning students to collaborate in dyads or pairs for problem-solving, as an instructional strategy in management higher education, can be applied for generating solutions to problems and issues raised by present management research as illustrated below.…”
Section: Need For Pairing To Foster Creativity and Innovation In The mentioning
confidence: 99%
“…In Leem and Rogers' (2017) quantitative study on the moderating impact of supply chain role on the relationship between social capital and company performance in Korea, they raised a complication of the different supply chain roles, such as logistics providers, suppliers, manufacturers and distributors, having varied effects on the relationship between the three dimensions of social capital, namely structural, relational and cognitive capital, and firm performance. For example, they found that the manufacturer supply chain role positively influenced the link between all three dimensions of social capital and company performance.…”
Section: Need For Pairing To Foster Creativity and Innovation In The mentioning
confidence: 99%
See 1 more Smart Citation
“…External structure capital refers to the overall pattern of relationship between different actors in the social network, which is the inhumanity of social relationship network, mainly including tightness degree, stability and connectivity of network (Whipple et al, 2015). In this study, external structure capital under the background of supply chain can be identified as the density and stability of external network connection between members such as suppliers, manufacturers, distributors and retailers in supply chain (Leem & Rogers, 2017). Judging from external network density, closer the link between members and other partners in supply chain is, greater the scope of knowledge acquisition will be, which is more conducive for sharing and exchange of knowledge among member enterprises and promoting trust between member enterprises, reducing "free rider" and other non-moral opportunism behaviors.…”
Section: External Structure Capital Inter-organizational Knowledge Tmentioning
confidence: 99%